Characterization of Crude Extract of Mucor pusillus Rennin - Khothibul Umam Al Awwaly; Mustakim Mustakim; Rachmat Agus Budiutomo (Faculty of Animal Science Universitas Brawijaya, 2008)
The research preparation involved production of rennin, determination of optimum pH of crude extract of rennin, determination of optimum temperature of crude extract of rennin, and determination of enzyme kinetics. The obtained data was analyzed by descriptive analysis. Data was explained and elaborated according to science or new knowledge.Â The result from characterization of rennin enzyme of Mucor pusillus showed that optimum enzyme reaction at pH 6.0, temperature at 32oC and concentration of substrate optimum at 2%. Each activity of proteolitic enzyme of Mucor pusillus at pH, temperature and concentration of substrate were: 0.09599 unit/ml, 0.06942 unit/ml, and 0.07577 unit/ml, respectively. The obtained value of Vmax and Km were 0.0836 Unit/ml and 0.356, respectively. Conclusion of this research was crude extract of M. pusillus rennin had the optimum pH at 6,0, optimum of temperature at 32oC and optimum of substrat consentration at 2%. Â Keywords: rennin, Mucor pusillus, pH, temperature